2012
DOI: 10.1016/j.physleta.2012.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic behavior of ion exchange phenomena in polymer gel electrolytes through irradiated polymeric membrane

Abstract: A desktop experiment has been done to show the nonlinearity in the I-V characteristics of an ion conducting electrochemical micro-system. Its chaotic dynamics is being reported for the first time which has been captured by an electronic circuit. Polyvinylidene fluoride-cohexafluoropropene (PVdF-HFP) gel electrolyte comprising of a combination of plasticizers (ethylene carbonate and propylene carbonate) and salts have been prepared to study the exchange of ions through porous poly ethylene terephthalate (PET) m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Therefore, investigation in the ore-forming process with solid phase and the effect of dynamics has great significance. Chaos theory is an important branch of nonlinear analysis, and is widely applied in the last few decades in a variety of systems, e.g., mechanical, chemical, physical, as well as in social sciences [8][9][10][11]. In particular, chaotic techniques, developed to extract qualitative and quantitative information from time series, have been applied recently to the study of a large variety of irregular, erratic signals and by now have demonstrated to be very useful to reveal deep dynamical features [12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, investigation in the ore-forming process with solid phase and the effect of dynamics has great significance. Chaos theory is an important branch of nonlinear analysis, and is widely applied in the last few decades in a variety of systems, e.g., mechanical, chemical, physical, as well as in social sciences [8][9][10][11]. In particular, chaotic techniques, developed to extract qualitative and quantitative information from time series, have been applied recently to the study of a large variety of irregular, erratic signals and by now have demonstrated to be very useful to reveal deep dynamical features [12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, investigation in the oreforming process with solid phase and the effect of dynamics has great significance. Chaos theory is an important branch of nonlinear analysis, and is widely applied in the last few decades in a variety of systems, e.g., mechanical, chemical, physical, as well as in social sciences [7][8][9][10]. In particular, chaotic techniques, developed to extract qualitative and quantitative information from time series, have been applied recently to the study of a large variety of irregular, erratic signals and by now have demonstrated to can be very useful to reveal deep dynamical features [11].…”
Section: Introductionmentioning
confidence: 99%